The Influence Of Intrinsic And Extrinsic Motivation On The Performance Nurses In The Impatient Room Of Dr. Djoelham Binjai Hospital - Muhammad Faisal Lubis (Institute of Computer Science (IOCS), 2022)
The performance of nurses in RSUD Dr. Djoelham Binjai is still unable to provide the best health services to patients due to the lack of optimal work motivation of nurses and the lack of awareness of nurses about work status as a function of health services. To determine the relationship between intrinsic and extrinsic motivation with the performance of honorary nurses. This research uses survey research with explanatory research type. The population in this study were all honorary nurses in the Inpatient Room totaling 150 people using the total population sampling technique Random sampling with the Slovin formula, which was 109 people. Univariate analysis to explain the independent variables, namely intrinsic motivation, extrinsic and nurse performance. bivariate analysis using chi-square test and multivariate test using multiple logistic regression. Showed that intrinsic motivation (p=0.001) had an effect on the performance of nurses at Djoelham Binjai Hospital with an Ods Ratio of 13,486. Extrinsic motivation (p=0.008) affects the performance of nurses at Djoelham Binjai Hospital with an Ods Ratio of 11.457, thus intrinsic is the most influential variable compared to extrinsic motivation variables. It is expected that hospitals should intensify technical training to improve the performance of health workers, one of which is a nurse. Hospitals should encourage, send, evaluate nurses to take part in training held by external parties to the hospital and head nurses should be more flexible in accepting nurse input to increase participatory efforts from employees under them.